Gap closure in missing lateral incisors comparing the use of mesialising canines and prosthetic implants: A Systematic Review (Bangladesh Journal of Medical Science, 2024)
Background: The  most  prevalent  form  of  birth  defect  is  hypodontia, or  the  lack  of  teeth.  Patients  who  suffer  from  agenesis  of the  maxillary  lateral  incisors  worry  about  how  their  new teeth and face will look after therapy. The main purpose of orthodontic treatment, known as gap closure, is to preserve as many teeth as possible. The two most important methods regarding gap closure are mesialising canines and prosthetic implants.Objective: Mesialising  canines  and  prosthetic  implants  for  lateral maxillary  incisor  gap  closure  are  the  subjects  of  this systematic study.Methodology: In addition to using a systematic search technique on Google Scholar,  PUBMED,  and  the  Web  of  Science,  we  formally included  or  excluded  studies,  extracted  data,  assessed validity,  and  evaluated  quality.  A  systematic  review  was conducted on all of the studies. In order to evaluate the quality, the Cochrane risk of bias tool was utilized.Results: According  to  our  set  inclusion  criteria,  11  most  relevant studies  were  found  in  the  databases.  Data  was  extracted from  each  study  separately  in  an  Excel  Sheet.  All  studies mentioned  discussed  the  use  of  the  two  best  potential treatments,  their  advantages  and  disadvantages,  and  the parameters determining the best treatment.Conclusion: Although prosthetic implants did enhance a few metrics, this comprehensive  study  did  not  find  a  statistically  significant difference  between  the  two  treatments.  The  comparative efficacy  of  two  methods  for  closing  the  space  left  by removing maxillary lateral incisors requires more study.Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 765-774